Perceived Changes in Emotions, Worries and Everyday Behaviors in Children and Adolescents Aged 5-18 Years with Type 1 Diabetes during the COVID-19 Pandemic - Anastasia Sfinari; Panagiota Pervanidou; Giorgos Chouliaras; Emmanouil Zoumakis; Ioannis A. Vasilakis; Nicolas C. Nicolaides; Christina Kanaka-Gantenbein (MDPI AG, 2022)
The COVID-19 pandemic and the consequent restrictive measures may be related to increased stress and anxiety and to changes in daily behaviors. Children with type 1 diabetes (T1D) are a vulnerable group due to their difficulties in achieving glycemic control and to their medical and psychological comorbidities. The purpose of the current study was to the investigate the changes on emotional and behavioral parameters in children with T1D due to the Coronavirus crisis. A total of 152 children and adolescents, aged 5-18, were studied: 114 (62 boys) with T1D and 38 (19 boys) healthy volunteers (HV) (controls). The study was performed at the Diabetes Center, Aghia Sofia Children's Hospital, during the first national lockdown in Greece. The CRISIS questionnaire was completed by parents/caregivers. The data were collected in May 2020 and referred to two time-points: three months prior (before the pandemic), and the past two weeks. During the lockdown, it was observed significant aggravation in the "Emotion/Worries (EW)" symptoms in both groups (logEW-before vs. logEW-during the crisis, T1D: 2.66 ± 0.23 vs. 3.00 ± 0.21, p < 0.001 and HV: 2.62 ± 0.16 vs. 2.83 ± 0.18, p < 0.001). Deterioration of "ΕW" was recorded for 93.0% of those with T1D and 92.1% of the HV. "EW" during the lockdown were affected by: previous psychological condition, COVID-related concerns, and "Life Changes due to the COVID-19 crisis in the past two weeks (LC)". Deterioration was observed in the "daily behaviors" and "use of digital media" for all of the children. The crisis and the associated restrictions negatively affected both the lifestyle parameters and the behavioral and emotional variables of the children with T1D.